The Impact of Various Facets of Customer-Based Brand Equity on Brand Resonance - S. M. Hasin Ishrak; Muhammad Hasan Al-Mamun (International Journal of Business and Society, 2022)
Measuring the extent to which customer-based brand equity (CBBE) influences brand resonance (BR) in the context of carbonated soft drinks industry in Bangladesh was the principal objective of this research. In order to do so, a new BR model was developed. In addition, measuring CBBE was an ancillary objective. CBBE was measured by using the arguably two dominant CBBE instruments: CBBE Model-1 by Yoo and Donthu (2001) and CBBE Model-2 by Netemeyer et al. (2004). BR was measured by an instrument that was developed from the work of Lehmann et al. (2008). The measurement models of both CBBE instruments fit the data satisfactorily with some negligible issues. The BR was measured from two distinct datasets: Dataset-1 and Dataset-2. Though both CBBE instruments had some model fit issues in the causal relationship analyses of CBBE and BR, both CBBE Model-1 and CBBE Model-2 had outstanding explained variance estimates on BR measure. The impact of CBBE on BR is an untapped territory of brand management; therefore, measuring the influence of CBBE on BR along with separately measuring CBBE and BR in multiple product or service categories across industries using the instrument of the current research has great values for practitioners.